METHODOLOGICAL BASES FOR DEVELOPING SOFT AND DIGITAL SKILLS AMONG STUDENTS OF HIGHER EDUCATION INSTITUTIONS IN THE CONTEXT OF DIGITALIZATION OF EDUCATION (International journal of artificial intelligence, 2026)
This article examines the theoretical and methodological foundations for developing soft and digital skills in university students in the context of digitalization of the educational process. It analyzes modern approaches to understanding these competencies, revealing their interrelationships and significance for the professional training of future specialists. Particular attention is paid to the methodological conditions and pedagogical tools that facilitate the effective development of soft and digital skills in the university educational environment. It concludes that a systematic and integrative approach to developing these skills within academic disciplines and extracurricular activities is necessary.